Distributional characteristics for Ireland: A note - David Madden (University College Dublin, UCD School of Economics, 2009)
The distributional characteristic is a measure which can be used in many applications in social cost-benefit analysis. In the application here, the distributional characteristics of a number of broad aggregates of goods are calculated for Ireland. These calculations can aid in assessing the distributional implications of price and tax changes.
hdl:10197/2607
Keywords: D12; I18; I32; 330; Distributional characteristic; Welfare weight; Tax reform